Is Spiritual Intelligence No Longer Relevant in Business Performance? - Saad, Mazni; Husain, Rosita; Mahayuddin, Nafiza; Ahmad, Aznita; Muthu Kumarasamy, Mokana (International Journal of Engineering and Technology, 2018)
The current study was to examine the mediating role of Spiritual Intelligence (SQ) in engaging employees at the workplace. Particularly, this study aimed to at investigating the SQ in the relationship between practices and business performance among the food handlers. The main objective of this research is to examine the mediating effect of the SQ on the business performance (food, services, and atmosphere). Four main SQ dimensions from the ISIS measurement scale were used as a basis to collect the data. A total of 816 data was collected from the food handlers from different government’s off-premises. Analyzed with the Smart PLS, the analysis showed that SQ mediated the relationship between practices and business performance in these three areas. In assessing the structural model estimate, the results of analysis revealed that the direct effect is statistically difference from zero (β_c≠0). Thus, rejected the null hypothesis β_c=0 with a statistically significance showed that there is a mediating effect on the relationship between practices and business performance. The discussion is made in explanation of these results within the context of other researches and suggestions for further research.